1990
DOI: 10.1083/jcb.110.4.1295
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ transients are not required as signals for long-term neurite outgrowth from cultured sympathetic neurons.

Abstract: Abstract.A method for clamping cytosolic free Ca 2+ ([Ca2+]~) in cultures of rat sympathetic neurons at or below resting levels for several days was devised to determine whether Ca 2+ signals are required for neurite outgrowth from neurons that depend on Nerve Growth Factor (NGF) for their growth and survival. To control [Ca2+]i, normal Ca 2+ influx was eliminated by titration of extracellular Ca 2+ with EGTA and reinstated through voltage-sensitive Ca 2+ channels. The rate of neurite outgrowth and the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Our results showing that a strong depolarizing stimulus capable of markedly increasing intracellular calcium (Tolkovsky et al, 1990) is not sufficient in itself to induce Fos-IR in isolated sympathetic neurons if NGF has been withdrawn for a few hours, also suggest that Fosexpression cannot be expected to serve as a general marker of neuronal activity in all situations. Although it has been suggested that the differences observed in the propensity of different peripheral neurons to induce Fos-IR in the CNS after stimulation (Hunt et al, 1987) is due to the use of anaesthetics (Dragunow and Faull, 1989), some of the selective effects may indicate a similar dependence on an obligatory enabling signal, such as that provided by NGF.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our results showing that a strong depolarizing stimulus capable of markedly increasing intracellular calcium (Tolkovsky et al, 1990) is not sufficient in itself to induce Fos-IR in isolated sympathetic neurons if NGF has been withdrawn for a few hours, also suggest that Fosexpression cannot be expected to serve as a general marker of neuronal activity in all situations. Although it has been suggested that the differences observed in the propensity of different peripheral neurons to induce Fos-IR in the CNS after stimulation (Hunt et al, 1987) is due to the use of anaesthetics (Dragunow and Faull, 1989), some of the selective effects may indicate a similar dependence on an obligatory enabling signal, such as that provided by NGF.…”
Section: Discussionmentioning
confidence: 56%
“…Nor is it likely that a reduction of [Ca2+Ii evoked by the removal of NGF(Koike et al, 1989) is the cause of the reduced responsiveness to serum or depolarization because both stimuli elevate [Ca2+]i in the absence of NGF(Koike et al, 1989;Tolkovsky et al, 1990).…”
mentioning
confidence: 95%
“…These results confirmed earlier suspicions that calcium transients were not necessary in the initiation of outgrowth. Likewise, recent studies on rat sympathetic neurons demonstrate that calcium transients are not necessary for neurite extension (Tolkovsky et al, 1990). When calcium levels were clamped in these cells, by reducing extracellular calcium with EGTA and depolarizing the cell with high potassium, neurite outgrowth was still initiated in response to NGF.…”
Section: Lanthanum Treatmentmentioning
confidence: 95%
“…[Ca2+]i was measured in cell bodies at 370C using a Deltascan system with dual excitation and single emission (Tolkovsky et al, 1990). Excitation at 340 or 380 nm changed every 25 ms, and emission was collected at 511 nm with a photomultiplier tube.…”
Section: Measurement Of [Ca2l]mentioning
confidence: 99%